Exploring Blazor : creating server-side and client-side applications in .NET 7 - Litvinavicius, Taurius (Apress, 2023)
Build and develop web applications with Blazor in C#. This book covers both server-side and client-side Blazor, along with its latest features and the structure of the technology. Youll see that Blazor is a web UI framework based on C#, Razor, and HTML, and how it runs front-end logic using C#, either on the server or on the browser, using WebAssembly. This new edition not only covers the new structure for the Blazor environment, it also demonstrates the latest features, such as adding API features to a Blazor server project; creating code-behind files for C# and CSS; new ways to pick, save, and handle files in Blazor; and much more. The code and project layout have been updated in .NET 7 for this new edition. The book starts with an introduction to Blazor, along with its various categories and its basics and syntax, including Razor syntax implementation. You will go through Blazor navigation and components, and learn its life cycle events and other components. You will learn features specific to each Blazor type. You will see how Blazor works with storage, files, and JavaScript, and you will create a Blazor code library. You will also create web applications in Blazor using practical implementations and real-life scenarios for both the server side and the client side. After reading this book, you will be able to build web applications with Blazor in C#11 and .NET Core 7.0. You will: Bind data and handle events in C# Blazor Handle components and page navigation in Blazor Connect Blazor front-end to APIs Interact with files using Blazor Understand the layout of Visual Studio Blazor project templates.